Ovarian Ectopic Gestation after Assisted Reproductive Technique with Intracytoplasmic Sperm Insemination - Kubaisi, Muna Kh. Al; Yusoff, Md Azam Md; Al-Shibli, Saad M.; Ismail, Nurul Jannah; Md Ibrahim, Iza Emilia; Azizan, Azha S.; Affandi KA Affandi, Khairunisa Ahmad; Ramli, Roszaman (International Journal of Innovative Research in Medical Science, 2022)
Assisted reproduction technique (ART) is a known risk factor for ectopic pregnancy (EP). Ovarian ectopic pregnancy (OEP) is a rare but well-known variant of EP, which carries diagnostic challenges & is mostly diagnosed intraoperatively. Fibroid is a common medical problem, but it is not yet a recognised risk factor for OEP. Risk factors as pelvic inflammatory disease, endometriosis or fibroids can alter fallopian tube patency results in EP. In this case study the embryo implantation occurs in the ovaries with retrograde embryo migration from the uterine cavity to the peritoneum. We present an OEP with male factor subfertility that went for frozen embryo transfer. The woman had multiple small fibroids referred to the tertiary centre for fluctuation in β-hCG level and suspicion of cornual pregnancy. However, the patient was asymptomatic & haemodynamically stable. Initial diagnosis of EP with viable fetus necessitate laparoscopic interference revealed left sided OEP with normal left fallopian tube (FT). The right ovary and FT looked normal. Surgical interference with partial oophorectomy was done and the histopathological report confirms the diagnosis of OEP. The following embryo transfer after 3 months ended by viable intrauterine pregnancy.